Republic of Mozambique : Staff Report for the 2013 Article IV Consultation, Sixth Review Under the Policy Support Instrument, Request for a Three-Year Policy Support Instrument and Cancellation of Current Policy Support Instrument. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2013)
The staff report for the 2013 Article IV Consultation for the Republic of Mozambique focuses on the development agenda and appropriate policy priorities to successfully transition to a resource-rich era. These priorities include skillful medium-term management of the impact of developing coal and gas resources, high public investment spending on growth, external competitiveness, and through increased commercial borrowing, on debt sustainability and investment planning. Mozambique has a high rate of public investment of which more than half is financed domestically. The authorities are working to strengthen their project selection and economic profitability analysis capacity, and to assess the impact of related borrowing on public debt.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet